2019
DOI: 10.1111/bjh.16003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decline in estimated glomerular filtration rate is common in adults with sickle cell disease and associated with increased mortality

Abstract: Summary We evaluated the prevalence of rapid decline in kidney function, its potential risk factors and influence upon mortality in sickle cell disease (SCD) in a retrospective single‐center study. Rapid decline of kidney function was defined as estimated glomerular filtration rate (eGFR) loss of >3·0 ml/min/1·73 m2 per year. A multivariable logistic regression model for rapid eGFR decline was constructed after evaluating individual covariates. We constructed multivariate Cox‐regression models for rapid eGFR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Chronic kidney disease (CKD) is a frequent concomitant complication of sickle cell anemia (SCA) and constitutes an independent risk factor for death in the adult sickle cell population. 1,2 Structural and functional changes in the kidney begin in children with SCA and are evidenced by whole kidney hyperfiltration and hyposthenuria. [3][4][5][6] It is postulated that persistent single nephron hyperfiltration contributes to the development of sclerosis; over time, continued glomerulosclerosis contributes to a decrease in renal reserve and progression to CKD.…”
mentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a frequent concomitant complication of sickle cell anemia (SCA) and constitutes an independent risk factor for death in the adult sickle cell population. 1,2 Structural and functional changes in the kidney begin in children with SCA and are evidenced by whole kidney hyperfiltration and hyposthenuria. [3][4][5][6] It is postulated that persistent single nephron hyperfiltration contributes to the development of sclerosis; over time, continued glomerulosclerosis contributes to a decrease in renal reserve and progression to CKD.…”
mentioning
confidence: 99%
“…LV wall thickness and hypertrophy are known to be powerful predictors of cardiovascular morbidity and mortality in the general population and this has been noted in SCD as well 22 . Renal impairment is common in SCD, manifested in early stages as microalbuminuria, followed by decreasing eGFR proceeding to end‐stage renal failure in some patients, all of which significantly decreases life expectancy in SCD 23 . Proteinuria has also been associated with mortality; 24 however, urine measures of albumin and albumin/creatinine ratio were less important than BUN for risk assessment in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A close relationship has also been found between rapid GFR decline and the risk of death. 9 In the general population, pre-eclampsia (PrE), defined as new-onset hypertension and proteinuria after 20 weeks of pregnancy, is associated with a higher risk of CKD and end-stage kidney disease (ESKD). 10,11 In a single-centre case-control study, Ngo et al showed that PrE was more frequent in SCD patients (9Á4%) than in the control group (2Á3%).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies recently showed that the deterioration of renal function was faster in SCD patients with severe genotypes [homozygous (HbSS) and sickle‐β 0 ‐thalassemia (HbSβ 0 )] than in those with mild genotypes, sickle cell trait or without SCD 7,8 . A close relationship has also been found between rapid GFR decline and the risk of death 9 . In the general population, pre‐eclampsia (PrE), defined as new‐onset hypertension and proteinuria after 20 weeks of pregnancy, is associated with a higher risk of CKD and end‐stage kidney disease (ESKD) 10,11 .…”
Section: Introductionmentioning
confidence: 99%